Women Writing War : From German Colonialism through World War I - Hammerstein, Katharina von; Kosta, Barbara; Shoults, Julie (2018)
Recent scholarship has broadened definitions of war and shifted from the narrow focus on battles and power struggles to include narratives of the homefront and private sphere. To expand scholarship on textual representations of war means to shed light on the multiple theaters of war, and on the many voices who contributed to, were affected by, and/or critiqued German war efforts. Engaged women writers and artists commented on their nations' imperial and colonial ambitions and the events of the tumultuous beginning of the twentieth century. In an interdisciplinary investigation, this volume explores select female-authored, German-language texts focusing on German colonial wars and World War I and the discourses that promoted or critiqued their premises. They examine how colonial conflicts contributed to a persistent atmosphere of Kriegsbegeisterung (war enthusiasm) that eventually culminated in the outbreak of World War I, or a Kriegskritik (criticism of war) that resisted it. The span from German colonialism to World War I brings these explosive periods into relief and challenges readers to think about the intersection of nationalism, violence and gender and about the historical continuities and disruptions that shape such events.